THE DUAL TITLE ACTION IN COSTA RICA: A PARADOXICAL SITUATION WITHIN REAL RIGHTS - Arguello Rojas , Mariano (2025)
This investigation lays the legal foundations to delimit the operational field of the so-called “double title action.” Such action has its place in court when two or more persons, whether natural or legal, have perfectly registered their private property title in the National Registry, however, the respective real right that derives from that registration covers two or more areas of total land or partially coincident in materiality. The analysis carried out allows us to critically visualize the prevailing jurisprudential trend, establishing some connections with other substantive and procedural institutes. Finally, some possible solutions are presented in those cases in which the double title action route it’s not completely satisfactory.